EFFECTIVE WAYS TO LEARN ENGLISH TENSES: MASTERING THE KEY TO FLUENCY (Proceedings of International Educators Conference, 2023)
Learning a new language can be a daunting task, and when it comes to English, one of the most critical aspects is understanding and using English tenses effectively. Tenses are a fundamental component of English grammar, as they provide a framework for expressing when an action occurred and its relation to the present and future. Mastering English tenses is essential for clear and precise communication. In this article, we will explore effective ways to learn English tenses and provide you with valuable insights on how to become a proficient user of tenses.